COVID-19 Collaborative critical care prediction and resource planning during the COVID-19 pandemic using computer simulation modelling: future urgent planning lessons. Issue 2 (2021) - Irvine, Nicola; Anderson, Gillian; Sinha, Chandrava; McCabe, Holly; Meer, Robert Van der
No abstract available